Reinforced concrete building design project & project based learning (case study) - Ahmad Basri, Arif Amir Farhan (2022)
From the designated works that have been done, all the design that been calculated by manual are the critical elements that show if all the elements are pass, other also will follow the designated design. This is because if the calculation is not pass, the student needs to redesign the construction elements because the student will be the engineer that will conduct the construction site to create a building that have safety aspect so that the building is safe for user to stay and used. With the detailing that been design also will help in constructing the building to make the contractor easy to understand on how the reinforcement and shear link that required for the specified construction element. For PROKON calculation, several element of the construction work cannot be compared to the manual due to difference of method, calculation and formula that even not come close to the unit that been calculated in manual. The PROKON data also show no error for the input as the value is not turn red in color. It is true that the PROKON is the software that can be use by the student to check either the manual design is no having problems or not, but for some circumstance, the value that been calculated by the PROKON cannot be compared with manual calculation. This is because the student did not expose to the method and formula that been used by the software and student cannot determine either the manual design is achieved the required specification or not. Also, the computation of the calculation code did not be studied in the programme code which is EC l l O that make it difficult and hard for the student to take other option on how the software been programmed. For the taking off and Bill of Quantities, the student can know on ho much the cost of material to construct the building by applying the Civil Engineering Quantities and Estimation (ECM366) knowledge towards this project. With this, the student has the experience in estimating experience even though not by getting it by internship course. The student also can know the latest rate of material of the construction material so that they can planned of the construction budget to avoid any over-budget of the project.